The Dominance of The European Council in The Decision-Making Process of Common Foreign and Security Policy of The European Union - I.G.A.Ag Dewi Sucitawathi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The European Union has changed significantly, especially regarding authoritybetween supranational and intergovernmental institutions. Intergovernmental institutions now begin to shift the authority of supranational institutions and seem to dominate the decision-making / foreign policy within the European Union. The cause of the emergence of dominance from intergovernmental institutions due to the existence of challenges and issues that are complex and sensitive is unable to be solved at the supranational level. The presence of the European Council which consisted by the Heads of State of each member country is expected to be able to resolve the foreign affairs of the European Union without disturbing diplomatic relations with other countries. The magnitude of the influence of the European Council is also supported in the points of the article in the European Union Treaty, which implicitly position the European Council as the highest authority in the European Union. The purpose of this study is to understand the dominance of the European Council in the Decision Making Process with the Common Foreign and Security Policy in the European Union. The theory used in this research is Intergovernmentalism. This study used qualitative methods, with descriptive analytical type, and data collection techniques usef sources in the form of primary and secondary data. Based on the results of the study, it was concluded that the European Council had dominated the decision-making process regarding the Common Foreign and Security Policy in the European Union. Domination is seen in several examples of important cases such as resolving the crisis in Libya in 2011, resolving the global financial crisis in 2008, and addressing the issue of climate change in 2011. The European Council has become the EU's collective head of state in handling global issues such as political, security, monetary, and the environment issues.